Implementasi Pengorganisasian, Pembagian Tugas, dan Koordinasi Pengurus dalam Manajemen Pendidikan di Pondok Pesantren Bustanul Mansuriyah - Akmal, Maulidina; Mutammam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Management is an important thing in an organization or institution, one part of management itself is organizing. In this study, the implementation or application of organizing, division of tasks and coordination of administrators in educational management at the Bustanul Mansuriyah Islamic boarding school is described. Various previous studies have also examined management in Islamic boarding schools, but in this study the focus is on educational management, division of tasks and coordination of administrators in Islamic boarding schools as a form of organization that occurs at the Bustanul Mansuriyah Islamic boarding school. The purpose of this study is to find out in detail how the implementation of organization occurs at the Bustanul Mansuriyah Islamic boarding school in the field of education and to find out how the organizational system runs as a form of educational management, namely organizing in the form of division of tasks and coordination of administrators. This study uses a qualitative approach with a descriptive research type. Data collection techniques are carried out through interviews, observations, documentation and library research from valid sources from books, journals and others, as well as from several previous studies. The results of this study indicate that organization, division of tasks, and coordination among administrators are crucial factors in the functioning of an organization, including Islamic boarding school education.